PENGARUH INTEGRASI CHATGPT DALAM INQUIRY-BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI FLUIDA - Jemari Ary; Pratama Benny Herlandy; Willyansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to analyze the effect of integrating ChatGPT into the Inquiry-Based Learning (IBL) model on students’ critical thinking skills in fluid topics. The research employed a mixed-methods approach with a sequential explanatory design, in which quantitative data served as the primary data and were supported by qualitative findings. A quasi-experimental design with a pretest–posttest non-equivalent control group was implemented at SMA Negeri 3 Gaung. The participants consisted of an experimental class receiving Inquiry-Based Learning integrated with ChatGPT and a control class receiving Inquiry-Based Learning without ChatGPT integration. The instruments included a critical thinking test based on Ennis’ indicators, observation sheets, interview guidelines, and documentation. Quantitative data were analyzed using descriptive statistics, normality, homogeneity, independent sample t-test, and N-gain analysis, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The results showed that the experimental class achieved a higher posttest mean score (25.66) than the control class (21.39), with N-gain scores of 0.41 and 0.23, respectively. The independent sample t-test produced a significance value of 0.000 (< 0.05), indicating a significant effect of ChatGPT integration within the Inquiry-Based Learning model on students’ critical thinking skills. The qualitative findings further revealed that ChatGPT supported students in formulating questions, exploring information, analyzing data, and reflecting on learning outcomes throughout the inquiry process.